Effects of Nirvishi Yoga on pesticide residues of cabbage: A pilot study - Shivanand Basappa Patil; J Vignesh; Giramalla Sathygouda Patil (Wolters Kluwer Medknow Publications, 2023)
Introduction: The agricultural sector's industrialization has increased the chemical burden on natural ecosystems. Pesticide use on crops is increasing, resulting in more stable residues on vegetables and food crops. Pesticide residues are posing high risks to health. The Ayurvedic Shodhana process has had an important role in decontamination as well as the purification of poisonous substances for ages. Nirvishi Yoga (NY) is one such solution for the removal of pesticide residues from cabbage. Its efficacy is compared with other washing methods for cabbage. Methods: The cabbage samples were subjected to different washing methods, namely, tap water washing (TWW), saltwater washing (SWW), and NY washing (NYW). All the samples were washed separately, filtered, and then subjected to liquid chromatography-mass spectrometry analysis for the quantification of rynaxypyr (Rx), azoxystrobin (Az), and novaluron (Nv) pesticides. Results: TWW sample revealed a reduction of 48.71% of Rx, 7.61% of Az, and 3.14% of Nv. 70.74%, 26.54%, and 36.54% of reduction in the residues were observed for SWW. NYW has significantly reduced the concentrations to 89% of Rx, 82.05% of Az, and 85.54% of Nv. Conclusion: NYW is determined to be the most effective method of washing for removing residues of pesticides Rx, Az, and Nv from the cabbage. There is an urgent need of spreading awareness and education regarding the health risks of pesticide residues and their decontamination methods for the welfare of mankind.